Facial Palsy Treatment After Cranial Base Fracture : A Systematic Review - Suci Nurjanah; Wardha Novia; Trisna Ayu Kurnia Putri; Sima Smith; Ni Made Shinta Dewi; Ulul Azmi; Bambang Priyanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Facial nerve paralysis is a common event in cases of cranial base trauma. Especially facial nerve paralysis due to trauma or fracture of the temporal bone accounts for around 7-10% of cases. Analysis of studies related to the management of facial nerve paralysis due to skull base fractures still needs to be studied. The aim of this paper is to examine in more depth the management of facial nerve paralysis due to traumatic skull base fractures. This research analyzes studies through the PubMed, Google Scholar, and Proquest databases. After searching, 729 articles were found. Seven articles were found that were suitable and discussed the management of facial nerve paralysis due to cranial base trauma. Based on the results of the investigation, it was found that the management carried out was based on the severity scale of facial paralysis where medical or surgical treatment could be carried out according to the required indications.